The Current State of Physical Activity and Exercise Programs in German-Speaking, Swiss Psychiatric Hospitals: Results from a Brief Online Survey [Corrigendum] - Brand S; Colledge F; Beeler N; Pühse U; Kalak N; Sadeghi Bahmani D; Mikoteit T; Holsboer-Trachsler E; Gerber M (Neuropsychiatric Disease and Treatment, 2020)
Brand S, Colledge F, Beeler N, et al. Neuropsychiatr Dis Treat. 2016;12:1309– 1317. Page 1309, Abstract, Methods, the text “All psychiatric hospitals (N=55) in the German-speaking part of Switzerland were contacted in spring 2014” should read “All psychiatric hospitals (N=55) in the German-speaking part of Switzerlandwere contacted in spring 2012”.    The authors apologize for this error and advise it does not affect the results of the paper. Read the original article